2018
DOI: 10.1001/jamaoncol.2018.1986
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Germline Mutations in Cancer Susceptibility Genes in Patients With Advanced Renal Cell Carcinoma

Abstract: Of patients with non-clear cell RCC, more than 20% had a germline mutation, of which half had the potential to direct systemic therapy. Current referral criteria for genetic testing did not identify a substantial portion of patients with mutations, supporting the role of a more inclusive sequencing approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
125
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 52 publications
22
125
1
1
Order By: Relevance
“…These include two different variants in POLE in two different tumors; two different variants in CHEK2 in two 6 different tumors; one variant in BRIP1 and PTCH1 both in a single tumor; and additional rare variants, one per tumor (e.g., TP53, MET, EGFR, among others, Table S7). This is consistent with a report on the relatively high frequency of germline mutations in cancer susceptibility genes in non-clear cell renal cell carcinomas 16 .…”
Section: Mutation Rates Frequency Of Driver Mutations and Germline supporting
confidence: 93%
“…These include two different variants in POLE in two different tumors; two different variants in CHEK2 in two 6 different tumors; one variant in BRIP1 and PTCH1 both in a single tumor; and additional rare variants, one per tumor (e.g., TP53, MET, EGFR, among others, Table S7). This is consistent with a report on the relatively high frequency of germline mutations in cancer susceptibility genes in non-clear cell renal cell carcinomas 16 .…”
Section: Mutation Rates Frequency Of Driver Mutations and Germline supporting
confidence: 93%
“…Of the 243 clear cell cases in this cohort, 13.6% (33/243) had a PV, of which 2.9% were RCassociated PVs. Similar findings were observed for the cases described as renal cell carcinoma, 13.1% (22/168) had a PV, of which 2.4% were RC-associated. DDR gene PVs were found in 24/243 (~10%) of clear cell cases, and in 16/168 (9.52%) of renal cell cases.…”
Section: Correlation Of Renal Histologies With Pvs In Specific Genessupporting
confidence: 87%
“…This population is particularly likely to be interested in evaluation of genetic risk. Further, germline PVs in some DDR genes have been observed in RC, including the DNA mismatch repair (Lynch syndrome) genes MSH2 and MLH1 in renal urothelial carcinoma, and CHEK2 in advanced renal cell carcinoma (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). To address the hypothesis that PVs in DDR genes may contribute to the missing heritability of eoRC, we analyzed germline sequencing data from a cohort of 844 eoRC, many of whom had additional non-RC primary tumors or a family history of non-RC cancers.…”
Section: Introductionmentioning
confidence: 99%
“…SDH‐deficient renal carcinomas were first identified in 2004 (Vanharanta, et al, ) and accepted as a unique subtype of renal tumor in 2016 (Moch, Cubilla, Humphrey, Reuter, & Ulbright, ). Two recent studies have identified the variant SDHA p.Arg31stop, previously defined as the most prevalent mutation observed in SDH‐deficient (GISTs) (Miettinen & Lasota, ), in renal cancer patients (Carlo, et al, ; McEvoy, et al, ). Association of SDHx germline variants with thyroid cancer risk has also been described (Neumann, et al, ; Ni, et al, ), of particular relevance to the proband in this study.…”
Section: Resultsmentioning
confidence: 99%